NATIONAL FAMILY CAREGIVER SUPPORT PROGRAM STATE/LOCAL EXPERIENCE: MASSACHUSETTS. (11th November 2018) - Bonner, A; Yu, P; Bernardo, A E
Abstract: Within Massachusetts, the National Family Caregiver Support Program is integrated into Aging Service Access Points (ASAPs) and Area Agencies on Aging. The twenty six ASAPs integrate information and referral, case management, protective services, and coordinate home and community services. Most ASAPs are co-located with AAAs. This allows the NFCSP to integrate caregiver support with other essential programs such as the state home care program, Medicaid waiver, protective services, Dementia Friendly Massachusetts and others. In Federal Fiscal Year 2017, the MFCSP served 3, 453 caregivers, including direct services for 850 caregivers with 114, 156 units of service, and counseling for 3, 152 caregivers with 9, 043 units of service. During this presentation we will provide some local examples of integration of the FCSP within ASAPs and hear from a family caregiver about their experience with the program.